The Development of Augmented Reality (AR) Based Learning Modules in Office Technology and Correspondence Subjects - Ramadhani, Indah Kurnia; Rosy, Brillian (Universitas Negeri Surabaya, 2023)
This study aims to describe the development of learning modules based on Augmented Reality (AR), determine the feasibility of modules for office technology and correspondence subjects, and determine student responses to the development of learning modules. This research is a Research and Development (R&D) type of research with a 4-D development model from Thiagarajan which consists of 4 stages of development namely define, design, develop, and disseminate. The advantages of learning modules have been adapted to an Merdeka curriculum based on Augmented Reality (AR) technology. The research instrument used was a closed questionnaire. Research on the development of this learning module uses two data analysis techniques, namely descriptive analysis techniques and quantitative analysis techniques. The results of the development of Augmented Reality (AR) based office and correspondence technology learning modules are in accordance with the Alur Tujuan Pembelajaran (ATP) and BNSP criteria. The results of the validation of learning modules from material experts, linguists, and graphics experts amounted to 95% with the proper category. The results of the trial were limited to 20 students obtaining a percentage of 85.9% in the very good category. Based on this explanation, the learning module for class X MPLB office technology and correspondence subjects that has been developed is feasible and very good for use in learning activities.